Prospek Politik Islam dalam Lanskap Demokrasi Indonesia Kontemporer - M, Madhur (Syura: Journal of Law, 2025)
Islamic political parties represent an integral part of Indonesia’s pluralistic and democratic political landscape. This study addresses the core issue of how Islamic political parties have evolved ideologically and politically in the context of Indonesia’s post-reform democratic system. The central objective of this research is to analyze the ideological foundation, development trajectory, and socio-political relevance of Islamic parties in Indonesia, particularly in terms of their role in promoting Islamic values while navigating a secular democratic framework. Using a qualitative descriptive method with a literature-based approach, this study collects data from academic books, journal articles, and relevant documents. It examines key parties such as the Prosperous Justice Party (PKS), the United Development Party (PPP), and the National Mandate Party (PAN), all of which represent various streams of Islamic political thought and influence .The findings reveal that Islamic political parties in Indonesia, while rooted in Islamic teachings emphasizing social and economic justice, face ongoing challenges in balancing religious identity with broader national interests. Although they actively participate in electoral politics and have shown fluctuating but sustained electoral performance, criticisms persist regarding their perceived overemphasis on religious issues at the expense of socio-economic development. This research contributes to the understanding of how Islamic political parties adapt to changing democratic dynamics in Indonesia. It also provides insights for future political engagement strategies that harmonize religious values with inclusive national development goals.